Critical Thinking Skills in Solving Problems in Economics Learning - Siti halimah; Muhammad Hadianur; Muhamat Qahfi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Education is a crucial aspect of a nation's progress. This is because the quality of a nation's education determines the quality of its human resources. Schools are required to provide education that fosters students' character, fostering critical thinking, creativity, communication, and collaboration, enabling them to adapt in the 21st century.This study aims to examine students' critical thinking skills in solving problems in economics.The research method used a descriptive qualitative approach. Subjects were selected using a purposive sampling technique. Data collection methods used were tests and interviews. Data validity was verified using a data credibility test using reference materials and a member check.The results of this study revealed that subjects 1 and 2 had high critical thinking skills in solving problems in economics, while subject 3 had moderate critical thinking skills in solving problems in economics.